(untitled) (BIRDEM Medical Journal, 2024)
Background: Major abdominal surgeries induce neuro-humoral changes responsible for postoperative pain, various organ dysfunctions and prolong hospitalization. Inadequate pain therapy prolongs the hospital stay and increases the mortality rates. Epidural analgesia confers excellent pain relief leading to a substantial reduction in the surgical stress response. Type 2 diabetic patients have multiple comorbidities with cardiovascular complication and they are more vulnerable to pain. The purpose of this study was to compare the effect of ropivacaine and bupivacaine with fentanyl on haemodynamic and postoperative analgesic requirement of type 2 diabetic patients for major abdominal surgeries. Methods: This prospective, double blind, randomized study were conducted in sixty patients who were going to be operated for major abdominal surgeries from 1st January 2022 to 30th June 2022 at the department of Anaesthesiology and Surgical ICU, BIRDEM General Hospital, Shahbagh, Dhaka, Bangladesh. The study population was randomly divided into group R & group B with 30 patients in each group. Every patient received an epidural block in the sitting position at the T8-9 or T9-10 level via 18 G Touhy needle. Each patient in group R received 0. 2% ropivacaine with 2 μgm. fentanyl / ml solution through epidural catheter @ 6 - 14 ml / hr. and group B received 0.125% bupivacaine with 2 μgm. fentanyl / ml solution through epidural catheter@ 6 - 14 ml / hr. Results: Peroperative mean systolic blood pressure, mean diastolic blood pressure, mean arterial blood pressure and heart rate were more stable in group R but statistically not significant (p>0.05) and in post operative period group R patients had significantly lower mean visual analogue scale (VAS) score than group B which was statistically significant (p<0.05) but additional analgesic requirement were slightly higher in group B which was not statistically significant (p>0.05). Conclusion: The results of our study suggest that epidural analgesia using ropivacaine 0.2% infusion is more effective than bupivacaine when used for postoperative pain relief and ropivacaine can be used as a safe alternative to bupivacaine for major abdominal surgeries. BIRDEM Med J 2024; 14(1): 23-30